Finite element implementation for computer-aided education of structural mechanics: Mohr's circle and its practical use - Lee, Jae Young; Ryu, Hee Ryong; Park, Young Taek (Computer applications in engineering education, 2014)
This article introduces a computer program for computer‐aided education about Mohr's circle and its practical use. The instructional tool has been implemented as part of a finite element analysis program, VisualFEA. The proposed approach to teaching and learning Mohr's circle is distinguished from previous work by its association with practical analysis models. The Mohr's circle is displayed and operated on the basis of stress data obtained from finite element analysis whereas arbitrarily assumed numerical values are used in other programs. The analysis can be extended to elasto‐plastic models with various yield criteria. Thus, the program can be regarded not only as an instructional module for studying Mohr's circle itself, but also as a training tool for exercising its practical application. This article describes the characteristics of the program's educational features and suggests important points for teaching and learning Mohr's circle and related subjects using VisualFEA. © 2011 Wiley Periodicals, Inc. Comput Appl Eng Educ 22:494–508, 2014; View this article online at wileyonlinelibrary.com/journal/cae; DOI 10.1002/cae.10.1002/cae.20575